1983
DOI: 10.1346/ccmn.1983.0310507
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Studies of Aluminous Goethites and Hematites

Abstract: Abstract--Synthetic aluminous hematites and goethites have been examined by Fourier-transform infrared spectroscopy. For aluminous hematites prepared at 950~ a linear relationship exists between AI content and the location of the band near 470 cm ~, up to 10 mole % AI substitution which is shown to be the solubility limit. The spectra of aluminous goethites prepared in two different ways are qualitatively similar to each other, but differ as to the relationship between the position of the band near 900 cm -1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

1987
1987
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 16 publications
1
24
0
1
Order By: Relevance
“…Namduri et al [9] assigned the bands at 540 cm -1 and 570 cm -1 as analytical bands of hematite and magnetite, respectively. Fysh and Fredericks [18] working with hematite at high temperature, reported bands at 470 and 550 cm-1. Desai et al [19] showed bands of hematite at 476 and 616 cm -1 .…”
Section: B Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Namduri et al [9] assigned the bands at 540 cm -1 and 570 cm -1 as analytical bands of hematite and magnetite, respectively. Fysh and Fredericks [18] working with hematite at high temperature, reported bands at 470 and 550 cm-1. Desai et al [19] showed bands of hematite at 476 and 616 cm -1 .…”
Section: B Infrared Spectroscopy (Ft-ir)mentioning
confidence: 99%
“…Electron diffraction studies (Goltztaub, 1935;van Oosterhout, 1960;Cornell et al, 1983) have shown that goethite crystals are commonly elongated in the [001 ] direction, although factors such as pH, temperature, and the presence of foreign elements in the synthetic system can influence the morphology of the final product. Synthetic goethites doped with A1 have been widely studied (e.g., Fysh and Clark, 1982;Fysh and Fredericks, 1983;Murad and Schwertmann, 1983;Schulze, 1984;Mann, 1983). AI substitutes directly in goethite for Fe in octahedral sites because the ionic radius of A1 (0.67 A) (Shannon and Prewitt, 1969) is similar to that of Fe 3 § (0.78 A).…”
Section: Introductionmentioning
confidence: 99%
“…The positions of the IR absorption bands observed here result from both AI-and OH-substitution in the hematite lattice. Aluminium substitution causes a shift to higher absorption values in comparison with pure hematite [15,16], whereas an increasing hydroxyl group content in the hematite anion sublattice displaces the absorption bands towards lower frequencies [17]. From the infrared spectra presented in Fig.…”
Section: Resultsmentioning
confidence: 96%